2010
DOI: 10.1021/je100614r
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibria for Ethyl Acetate + Methanol at (0.1, 0.5, and 0.7) MPa. Measurements with a New Ebulliometer

Abstract: A new dynamic still for the determination of vapor−liquid equilibrium (VLE) data has been constructed in stainless steel. Both the liquid and vapor phases are recirculated. The operating procedure is based on the Cottrell pump principle. The liquid mixture is placed in an inverted double-walled vessel and heated. The equipment performance has been verified by measurements on mixtures that have been previously studied by various authors. VLE data have been determined for the ethyl acetate + methanol binary syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 17 publications
3
48
0
Order By: Relevance
“…These chemicals were used without further purification. The normal boiling point at 0.1 MPa was determined with a stainless steel ebulliometer [13]. A Kyoto Electronics DA-300 vibrating tube density meter with an uncertainty of ±0.1 kg m −3 and a Zusi 315RS Abbe refractometer with an uncertainty of ±0.0002 units were used for density and refractive index determinations, respectively.…”
Section: Chemicals and Apparatusmentioning
confidence: 99%
“…These chemicals were used without further purification. The normal boiling point at 0.1 MPa was determined with a stainless steel ebulliometer [13]. A Kyoto Electronics DA-300 vibrating tube density meter with an uncertainty of ±0.1 kg m −3 and a Zusi 315RS Abbe refractometer with an uncertainty of ±0.0002 units were used for density and refractive index determinations, respectively.…”
Section: Chemicals and Apparatusmentioning
confidence: 99%
“…2 and 3) that there is good agreement and similar trend from 0.0 to 0.6 MPa, which is a function of pressure, for both MA2P and EA2P systems. Therefore, from a comparison between literature data (Ortega and Susial, 1993;Hernandez and Ortega, 1997), which was obtained with a small capacity glass ebulliometer, and data obtained by us (Susial et al, 2014) at 0.3 and 0.6 MPa with a stainless steel ebulliometer (Susial et al, 2010) that has a volumetric capacity at least 8 times higher and provides about 6 times larger recirculation times, it may be concluded that the equilibrium still (Susial et al, 2010) used in this work is reliable to generate experimental data for VLE. Accordingly, an apparent symmetry at 1.5 MPa was observed in the MA2P system (see Fig.…”
Section: Treatment Of Vle Data and Predictionmentioning
confidence: 51%
“…Considering this, and as a continuation of previous works (Ortega and Susial, 1993;Susial et al, 2014), the isobaric vapor-liquid equilibrium (VLE) of different ester + alcohol binary mixtures under over-pressure conditions has been experimentally determined using a dynamic stainless steel ebulliometer (Susial et al, 2010). Specifically, the VLE properties (p-T-x-y) were obtained at 1.5 MPa for the binary mixtures of methyl acetate + 2-propanol (MA2P) and ethyl acetate + 2-propanol (EA2P).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations